Experiences of Working with Parents with Mental Disabilities in Private Education Institutions: A Qualitative Focus Group Study - Mustafa Karatas; Sultan Güçlü (Unnes Journal of Public Health, 2025)
The purpose of this study is to understand the experiences of parents with intellectual disabilities employees whom working in official private education institutions and the contribution to the scientific field. A qualitative method was used in this research. The study adopted a phenomenological design, highlighting the exploratory nature of qualitative research. Six focus groups were formed in this  study. -These six focus group sessions were conducted, with total of 36 participants. Coding analyses were done using the MAXQDA 2022 program. Then,content analyses  from the focus groups were conducted focusing to answer the research questions.This study recommended that counseling services should be provided specifically to intellectually disabled parents, focusing particularly specific on the social work profession. In addition, this study recommended for competent authorities to conduct further close monitoring and  case follow-ups for involved families to observe the ongoing situations between parents and children.